Současné trendy elektrických pohonných jednotek osobních vozidel - Drapela, Lukáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2023)
Bakalářská práce má za cíl uvedení přehledu současných koncepcí elektrických pohonů osobních automobilů spolu s uvedením konkrétních příkladů a jejich kritickým zhodnocením. První část práce se zabývá popisem fungování jednotlivých druhů elektromotorů. Práce pokračuje popisem koncepcí nejprve hybridních vozidel, a následně vozidel poháněných čistě elektricky. Poslední část práce se věnuje současným trendům ve zvyšování účinnosti a dojezdu elektromobilů. Tato část je doplněna stanovením energetické náročnosti modelu elektrického vozidla pro zvolené srovnávací parametry pomocí simulačního programu GT-Suite.

Bachelor’s thesis is focused on providing a comprehensive overview of the current architecture of electric drivetrains for passenger cars with offering specific examples and their critical evaluation. The first part of the thesis aims to describe the function of several different types of electric motors. This thesis continues with a description of the architecture of hybrid vehicles followed by vehicles powered purely by electricity. The final part of the thesis is dedicated to current trends in increasing efficiency and range of electric cars. This part is then supported by a calculation of energy demand of the electric vehicle model for selected comparative parameters using the GT-Suite simulation programme.
Recent trends in electric drive units of passenger vehicles
Keywords: Elektromobil; elektromotor; elektrický pohon; hybridní pohon; akumulátor; Electric vehicle; electric motor; electric drivetrain; hybrid drivetrain; battery